(untitled) (EAAE Annual Conference Proceedings, 2019)
This paper identifies two visions of the challenge of technology integration in architecture for education. Then, the appropriateness of conceiving architecture from a holistic perspective of the human dwelling is suggested, proposing an awareness of its technological aspects. Finally, some considerations of technology in architecture, in particular in teaching and learning are challenged, first analytically and then with an integrative intention.